2018
DOI: 10.1016/j.jconrel.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Lipid conjugation of TLR7 agonist Resiquimod ensures co-delivery with the liposomal Cationic Adjuvant Formulation 01 (CAF01) but does not enhance immunopotentiation compared to non-conjugated Resiquimod+CAF01

Abstract: conjugation of TLR7 agonist Resiquimod ensures co-delivery with the liposomal Cationic Adjuvant Formulation 01 (CAF01) but does not enhance immunopotentiation compared to non-conjugated Resiquimod+CAF01. Corel (2018),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 64 publications
(78 reference statements)
0
17
0
Order By: Relevance
“…In addition, certain adjuvants are compounds with a low molecular weight (MW), and incorporation in liposomes or other VADSs can guarantee their co-delivery with Ags to the same population of APCs, while avoiding a systemic distribution and off-target cellular uptake. For example, resiquimod, a small water-soluble agonist of the endosome-located TLR7/8, will rapidly distribute throughout the body after injection in an aqueous solution and, when conjugated to cationic liposomes composed of DDA/TDB, has achieved co-delivery with Ags in mouse models, though this bound combination did not significantly elevate the already strong adjuvanticity of the cationic liposomes [127].…”
Section: Ag Release and Liposome Integrity In Vivomentioning
confidence: 99%
“…In addition, certain adjuvants are compounds with a low molecular weight (MW), and incorporation in liposomes or other VADSs can guarantee their co-delivery with Ags to the same population of APCs, while avoiding a systemic distribution and off-target cellular uptake. For example, resiquimod, a small water-soluble agonist of the endosome-located TLR7/8, will rapidly distribute throughout the body after injection in an aqueous solution and, when conjugated to cationic liposomes composed of DDA/TDB, has achieved co-delivery with Ags in mouse models, though this bound combination did not significantly elevate the already strong adjuvanticity of the cationic liposomes [127].…”
Section: Ag Release and Liposome Integrity In Vivomentioning
confidence: 99%
“…This effect was not restricted to the 3M-052 ligand as the adsorption of another TLR7/8 agonist compound to alum (28) potentiates immune responses to glycoconjugate (52) or pertussis vaccines (53). In contrast, Wilkinson et al recently reported that the lipid conjugation of the TLR7 agonist resiquimod to CAF01 does not potentiate immune responses, despite a depot at the site of immunization (54). However, CAF01 already induces strong T H 1 responses (55) and contains the potent TDB immunomodulator which promotes APC activation through the C-type lectin receptor Mincle (56).…”
Section: Discussionmentioning
confidence: 97%
“…antigen IFN-g responses in the spleen can be 15 times higher whilst IL-17 is 6 times high [36]. There…”
Section: Accepted Manuscriptmentioning
confidence: 99%